Phosphodiesterase DosP increases persistence by reducing cAMP which reduces the signal indole. Issue 3 (21st October 2014) - Kwan, Brian W.; Osbourne, Devon O.; Hu, Ying; Benedik, Michael J.; Wood, Thomas K.
ABSTRACT Persisters are bacteria that are highly tolerant to antibiotics due to their dormant state and are of clinical significance owing to their role in infections. Given that the population of persisters increases in biofilms and that cyclic diguanylate (c‐di‐GMP) is an intracellular signal that increases biofilm formation, we sought to determine whether c‐di‐GMP has a role in bacterial persistence. By examining the effect of 30 genes from Escherichia coli, including diguanylate cyclases that synthesize c‐di‐GMP and phosphodiesterases that breakdown c‐di‐GMP, we determined that DosP (direct oxygen sensing phosphodiesterase) increases persistence by over a thousand fold. Using both transcriptomic and proteomic approaches, we determined that DosP increases persistence by decreasing tryptophanase activity and thus indole. Corroborating this effect, addition of indole reduced persistence. Despite the role of DosP as a c‐di‐GMP phosphodiesterase, the decrease in tryptophanase activity was found to be a result of cyclic adenosine monophosphate (cAMP) phosphodiesterase activity. Corroborating this result, the reduction of cAMP via CpdA, a cAMP‐specific phosphodiesterase, increased persistence and reduced indole levels similarly to DosP. Therefore, phosphodiesterase DosP increases persistence by reducing the interkingdom signal indole via reduction of the global regulator cAMP. Biotechnol. Bioeng. 2015;112: 588–600. © 2014 Wiley Periodicals, Inc.